Laboratory Characterization of Reservoir Rock and Fluids of Upper Assam Basin, India - Barman, J. (Springer Science and Business Media B.V., 2019)
The characterization of major oil producing reservoirs of Upper Assam Basin for Enhanced Oil Recovery (EOR) application is discussed in this study. The characterization of reservoirs is done in terms of reservoir rocks and fluids. The reservoir rocks comprise of underground porous media of the depleted reservoirs. Crude Oil (CO) samples containing different percentage of Formation Waters (FWs) were collected from well heads of the producing reservoirs. The reservoir fluids comprise of FW and CO. The characteristics of the porous media were done in terms of porosity and permeability. COs were separated from FW to analyse the parameters of both CO and FW. The FWs produced from the reservoirs were found to be of high salinity and high electrical conductivity, less acidic, contain low Dissolved Oxygen (DO) and Total Dissolved Solid (TDS) contents. Besides, the Characterization Factor (CF), Correlation Index (CI), class of the CO samples was determined using ASTM distillation method. CI exhibited aromatic nature whereas the CF exhibited more naphthenic nature of CO, besides CO was found to be Class D class of crude with low pour point. The asphaltenes and resins contents were found to be towards the higher side. While the viscosity of CO with increasing temperatures was experimented using Cannon-Fenske Routine Viscometer which conclude the viscosity behaviour of the crude sample. The CO samples were found to have low pour point. Therefore, by characterizing the reservoirs an understanding can be made on the applicability of EOR processes in the depleting oil fields of Upper Assam Basin. Â© 2019, Springer Nature Switzerland AG.